A new species of Leptobrachella (Anura, Megophryidae) from Mount Pu Ta Leng, northwest Vietnam - Nguyen, Luan Thanh; Tapley, Benjamin; Nguyen, Chung Thanh; Luong, Hao Van; Rowley, Jodi J.l. (Zootaxa, 2021)
The Hoang Lien Range in northwest Vietnam is known to harbour five species of Leptobrachella, a specious genus of terrestrial frogs. We collected specimens of Leptobrachella from Mount Pu Ta Leng on the second highest peak in the Hoang Lien Range and use morphological and molecular data to show that this population represents a previously undescribed species which we name Leptobrachella graminicola sp. nov. after the abundance of calling males on sedge-like plants. This new species is closely related to L. bourreti but the new species is distinguished from L. bourreti and other congeneric species by a combination of the following characters: (1) a body size range of 23.1–24.6 mm in six adult males and 28.6–32.9 mm in five adult females; (2) skin on dorsum smooth, with many tubercles and lacking dermal ridges; (3) toes with rudimentary webbing and broad lateral fringes; (4) belly white with brown spots; (5) throat dark brown with light grey-brown flecks and spots; (6) a row of large white spots on the outer edge of the tarsus extending from the heel to the inner metatarsal tubercle, sometimes forming a long white stripe; and (7) a bicoloured iris. The new, high-elevation species is likely to be range-restricted and threatened by habitat loss and the activities of tourists.